2012
DOI: 10.1103/physrevlett.109.126401
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Dependent On-Site Electron Correlations and Localization in Itinerant Ferromagnets

Abstract: Spin selectivity in angle-resolved Auger photoelectron coincidence spectroscopy (AR-APECS) is used to probe electron correlation in ferromagnetic thin films. In particular, exploiting the AR-APECS capability to discriminate Auger electron emission events characterized by valence hole pairs created either in the high or in the low total spin state, a strong correlation effect in the Fe M(2,3)VV Auger line shape (measured in coincidence with the Fe 3p photoelectrons) of Fe/Cu(001) thin films is detected and ascr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…These more localized valence flip excitations are then transferred to the photoelectron. The visible orbital flip effect is thus a manifestation of a different correlation in the two bands with different spin, established recently on a quantitative basis by experimental and theoretical studies on Auger emission 26 , and of different orbital character, as earlier suggested 70 . Orbitals appear nearly as quenched far from E F , where only spin flip excitations are clear, while spin and orbital degrees of freedom are entangled and both active at low energy.…”
Section: Computational Detailsmentioning
confidence: 64%
“…These more localized valence flip excitations are then transferred to the photoelectron. The visible orbital flip effect is thus a manifestation of a different correlation in the two bands with different spin, established recently on a quantitative basis by experimental and theoretical studies on Auger emission 26 , and of different orbital character, as earlier suggested 70 . Orbitals appear nearly as quenched far from E F , where only spin flip excitations are clear, while spin and orbital degrees of freedom are entangled and both active at low energy.…”
Section: Computational Detailsmentioning
confidence: 64%
“…Consequently, such localization leads to electronic states that do not disperse in energy over the reciprocal space. Examples are found in compounds of the heavy rare earth elements where strongly localized f-electron states are responsible for the weakly dispersing heavy fermion bands but also for the core levels of the elemental ferromagnets, for which spin-dependent renormalization was firstly observed 28 , 29 . By contrast, the 3d-electron states responsible for band ferromagnetism are only weakly localized, and characterized by a sizeable energy dispersion over the BZ.…”
Section: Discussionmentioning
confidence: 99%
“…For this material U W / 0.8 ≈ hence its Auger lineshape is in the intermediate region between a band-like and atomic like behavior. The complexity of the Auger spectra can be reduced by electron coincidence spectroscopy and significant experimental advances have been made in the past [6,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%